Non-aqueous electrolyte secondary battery and method for manufacturing the same

By using amorphous carbon layer and particles with high conductivity in the negative electrode material of the nonaqueous electrolyte secondary battery, combined with styrene butadiene rubber and carboxymethyl cellulose salt, the insufficient performance of the battery at low temperature, circulation and high temperature is solved. Problem, excellent regeneration characteristics, cycle characteristics and storage characteristics are achieved.

CN111755666BActive Publication Date: 2024-12-17SANYO ELECTRIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010072971.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-26
Filing Date
2020-01-21
Publication Date
2024-12-17
Estimated Expiration
2040-01-21

AI Technical Summary

Technical Problem

There is room for improvement in the low-temperature regeneration characteristics, circulation characteristics and high-temperature storage characteristics of the existing nonaqueous electrolyte secondary batteries.

Method used

The negative electrode material is coated with amorphous carbon layer and amorphous carbon particles with high conductivity on the surface of graphite particles. Combined with styrene butadiene rubber and carboxymethyl cellulose salt, it can be processed and composed of a specific process to form a high-quality Protect the coating and uniform conductive network to improve the performance of the battery.

Benefits of technology

It significantly improves the low-temperature regeneration characteristics, cycle characteristics and high-temperature storage characteristics to ensure the efficient performance of the battery under different conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111755666B_ABST
    Figure CN111755666B_ABST
Patent Text Reader

Abstract

The present invention provides a non-aqueous electrolyte secondary battery having excellent low-temperature regeneration characteristics, cycle characteristics, and high-temperature storage characteristics, and a method for manufacturing the same. In a non-aqueous electrolyte secondary battery as an example of an embodiment, the negative electrode comprises: graphite particles coated with amorphous carbon on the surface of the graphite particles, styrene-butadiene rubber, and at least one selected from carboxymethyl cellulose and a carboxymethyl cellulose salt, the amorphous carbon contained in the coated graphite particles comprises an amorphous carbon layer composed of a first amorphous carbon and amorphous carbon particles composed of a second amorphous carbon, the conductivity of the second amorphous carbon is higher than the conductivity of the first amorphous carbon, and the BET specific surface area of ​​the amorphous carbon particles is 37 to 47 m 2 / g, the average primary particle size of styrene-butadiene rubber is 150 to 210 nm, and the weight average molecular weight of at least one of carboxymethyl cellulose and carboxymethyl cellulose salt is 3.7×10 5 ~4.3×10 5 .
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a non-aqueous electrolyte secondary battery and a method for manufacturing the same. Background Art

[0002] In order to improve battery characteristics, a non-aqueous electrolyte secondary battery has been proposed, which comprises a negative electrode plate comprising non-coated flaky graphite particles whose surfaces are not coated and coated graphite particles whose surfaces are coated with a coating layer comprising amorphous carbon particles and an amorphous carbon layer (Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 5991717 Summary of the invention

[0006] Problems to be solved by the invention

[0007] For non-aqueous electrolyte secondary batteries, it is an important issue to improve battery characteristics such as low-temperature regeneration characteristics, cycle characteristics, and high-temperature storage characteristics. Conventional technologies including the technology disclosed in Patent Document 1 still have room for improvement in terms of battery characteristics.

[0008] Means for solving problems

[0009] A nonaqueous electrolyte secondary battery as one embodiment of the present application includes a positive electrode, a negative electrode and a nonaqueous electrolyte.

[0010] The negative electrode comprises: graphite particles coated with amorphous carbon on the surface of the graphite particles, styrene-butadiene rubber, and at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt.

[0011] The amorphous carbon contained in the coated graphite particles includes an amorphous carbon layer composed of first amorphous carbon and amorphous carbon particles composed of second amorphous carbon.

[0012] The electrical conductivity of the second amorphous carbon is higher than that of the first amorphous carbon.

[0013] The BET specific surface area of ​​the amorphous carbon particles is 37 to 47 m 2 / g,

[0014] The average primary particle size of the styrene-butadiene rubber is 150 to 210 nm.

[0015] The weight average molecular weight of at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt is 3.7×10 5 ~4.3×10 5 .

[0016] In a method for producing a nonaqueous electrolyte secondary battery as one embodiment of the present application,

[0017] The nonaqueous electrolyte secondary battery comprises a positive electrode, a negative electrode and a nonaqueous electrolyte.

[0018] The negative electrode comprises: graphite particles coated with amorphous carbon on the surface of the graphite particles, styrene-butadiene rubber, and at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt.

[0019] The amorphous carbon contained in the coated graphite particles includes an amorphous carbon layer composed of first amorphous carbon and amorphous carbon particles composed of second amorphous carbon.

[0020] The electrical conductivity of the second amorphous carbon is higher than that of the first amorphous carbon.

[0021] The coated graphite particles are prepared by attaching a BET specific surface area of ​​37 to 47 m 2 / g of the amorphous carbon particles and the graphite particles as the raw material of the first amorphous carbon are heated to convert the raw material of the first amorphous carbon into the first amorphous carbon,

[0022] The manufacturing method comprises the following steps:

[0023] A styrene-butadiene rubber containing the above-mentioned coated graphite particles, an average primary particle size of 150 to 210 nm, and a weight average molecular weight of 3.7×10 5 ~4.3×10 5 a step of preparing a negative electrode active material layer slurry containing at least one selected from carboxymethyl cellulose and a carboxymethyl cellulose salt;

[0024] The process of coating the negative electrode active material layer slurry on the negative electrode core; and

[0025] A step of drying the negative electrode active material layer slurry.

[0026] Effects of the Invention

[0027] According to the present application, a nonaqueous electrolyte secondary battery having excellent low-temperature regeneration characteristics, cycle characteristics, and high-temperature storage characteristics can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of an embodiment.

[0029] Figure 2 It is a plan view of a nonaqueous electrolyte secondary battery as an example of an embodiment.

[0030] Figure 3 It is a cross-sectional view schematically showing a negative electrode active material as an example of an embodiment.

[0031] Figure 4 This is a diagram schematically showing a negative electrode active material as an example of an embodiment, and is an enlarged cross-sectional view of the vicinity of an amorphous carbon particle.

[0032] Description of Reference Numerals

[0033] 1 outer packaging body, 2 sealing plate, 3 electrode body, 4 positive electrode core exposed portion, 5 negative electrode core exposed portion, 6 positive electrode collector plate, 7 positive electrode terminal, 8 negative electrode collector plate, 9 negative electrode terminal, 10, 12 internal insulating member, 11, 13 external insulating member, 14 insulating sheet, 15 gas discharge valve, 16 electrolyte injection hole, 17 sealing plug, 20 coated graphite particles, 21 graphite particles, 22 amorphous carbon layer, 23 amorphous carbon particles, 100 non-aqueous electrolyte secondary battery, 200 battery case DETAILED DESCRIPTION

[0034] The present inventors have found that: in the case where the negative electrode comprises graphite particles coated with amorphous carbon on the surface of graphite particles, styrene-butadiene rubber, and at least one selected from carboxymethyl cellulose and a carboxymethyl cellulose salt, a non-aqueous electrolyte secondary battery having excellent low-temperature regeneration characteristics, cycle characteristics, and high-temperature storage characteristics can be obtained by setting the following structure: the amorphous carbon contained in the coated graphite particles comprises an amorphous carbon layer composed of a first amorphous carbon and amorphous carbon particles composed of a second amorphous carbon, the electrical conductivity of the second amorphous carbon is higher than that of the first amorphous carbon, and the BET specific surface area of ​​the amorphous carbon particles is 37 to 47 m 2 / g, the average primary particle size of styrene-butadiene rubber is 150 to 210 nm, and the weight average molecular weight of at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt is 3.7×10 5 ~4.3×10 5 .

[0035] As the negative electrode active material, by using highly conductive coated graphite particles whose surfaces are coated with two types of amorphous carbon (first amorphous carbon and second amorphous carbon), a high-quality protective film from a non-aqueous electrolyte is uniformly formed on the surface of the negative electrode active material, thereby achieving a non-aqueous electrolyte secondary battery with excellent low-temperature regeneration characteristics.

[0036] In addition, in the coated graphite particles, the BET specific surface area of ​​the amorphous carbon particles composed of the second amorphous carbon present on the surface of the graphite particles is set to 37 m 2 / g or more, the charge transfer resistance on the surface of the negative electrode active material can be reduced, thereby further improving the low-temperature regeneration characteristics. In addition, by setting the BET specific surface area of ​​the amorphous carbon particles composed of the second amorphous carbon to 47m 2 / g or less, it is possible to suppress the concentrated combination of styrene butadiene rubber particles and amorphous carbon particles. Thus, in the negative electrode active material layer, the styrene butadiene rubber particles are prevented from being locally present near the amorphous carbon particles. Therefore, the styrene butadiene rubber particles are more easily evenly dispersed in the negative electrode active material layer. Therefore, even if charge and discharge cycles are performed, the negative electrode active material particles will not be isolated in the negative electrode active material layer, and a good conductive network will be maintained in the negative electrode active material layer. Therefore, a non-aqueous electrolyte secondary battery with excellent cycle characteristics is achieved.

[0037] By setting the average primary particle size of the styrene-butadiene rubber to 150 nm or more, it is possible to effectively prevent the styrene-butadiene rubber particles from entering the area having a BET specific surface area of ​​37 to 47 m 2 / g of the second amorphous carbon is contained in the concave portion possessed by the amorphous carbon particles composed of the second amorphous carbon. As a result, it is possible to suppress the concentrated combination of the styrene butadiene rubber particles and the amorphous carbon particles. Therefore, in the negative electrode active material layer, the styrene butadiene rubber particles are prevented from being locally present near the amorphous carbon particles. Therefore, the styrene butadiene rubber particles are more easily and evenly dispersed in the negative electrode active material layer. Therefore, even if charge and discharge cycles are performed, the negative electrode active material particles will not be isolated in the negative electrode active material layer, and a good conductive network will be maintained in the negative electrode active material layer. Therefore, it becomes a non-aqueous electrolyte secondary battery with excellent cycle characteristics.

[0038] By setting the average primary particle size of styrene-butadiene rubber to less than 210 nm, when the negative electrode active material layer is compressed during the manufacture of the negative electrode plate, it is possible to effectively suppress the styrene-butadiene rubber particles from being crushed and the styrene-butadiene rubber covering the large area of ​​the negative electrode active material surface. Thus, it is possible to suppress the increase in the area covered by styrene-butadiene rubber on the negative electrode active material surface. Therefore, a non-aqueous electrolyte secondary battery with more excellent low-temperature regeneration characteristics is achieved.

[0039] It should be noted that, by making styrene-butadiene rubber more evenly dispersed in the negative electrode active material layer, the resistance on the negative electrode active material surface easily becomes uniform. Therefore, by making styrene-butadiene rubber more evenly dispersed in the negative electrode active material layer, a high-quality protective coating from a nonaqueous electrolyte is more evenly formed on the negative electrode active material surface, and therefore, a nonaqueous electrolyte secondary battery with excellent high temperature storage characteristics is obtained.

[0040] By setting the weight average molecular weight of at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt to 3.7×10 5Above, at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt can be coated with amorphous carbon particles composed of the second amorphous carbon in a preferred state. Thus, the side reaction of amorphous carbon particles and non-aqueous electrolyte can be effectively suppressed. Therefore, a non-aqueous electrolyte secondary battery with excellent high temperature storage characteristics is obtained. It should be noted that the larger the weight average molecular weight of at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt becomes, the easier it is for at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt to be entangled in amorphous carbon particles, and at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt can be coated with amorphous carbon particles in a preferred state.

[0041] By setting the weight average molecular weight of at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt to 4.3×10 5 In the following manner, the generation of pinholes in the negative electrode active material layer can be effectively prevented.

[0042] Amorphous carbon is more hydrophobic than graphite, so it is believed that at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt will preferentially adhere to the amorphous carbon particles composed of the second amorphous carbon. In addition, the larger the weight average molecular weight of at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt, the easier it is for at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt to be entangled with the amorphous carbon particles, and the adhesion between at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt and the amorphous carbon particles becomes higher.

[0043] Hereinafter, an example of an embodiment of the present application will be described in detail with reference to the drawings. Figure 1 and Figure 2 , a rectangular battery including a rectangular battery case 200 , that is, a nonaqueous electrolyte secondary battery 100 is shown as an example of an embodiment.

[0044] like Figure 1 and Figure 2 As shown, the non-aqueous electrolyte secondary battery 100 has a square bottomed cylindrical outer package 1 and a sealing plate 2 that seals the opening of the outer package 1. The battery case 200 is composed of the outer package 1 and the sealing plate 2. The outer package 1 contains a flat electrode body 3 and a non-aqueous electrolyte, and the flat electrode body 3 is formed by winding a strip-shaped positive electrode and a strip-shaped negative electrode with a strip-shaped separator. The electrode body 3 has a positive electrode core exposed portion 4 formed at one end in the winding axis direction and a negative electrode core exposed portion 5 formed at the other end in the winding axis direction.

[0045] The positive electrode collector plate 6 is connected to the exposed portion of the positive electrode core 4, and the positive electrode collector plate 6 is electrically connected to the positive terminal 7. An internal insulating component 10 is arranged between the positive electrode collector plate 6 and the sealing plate 2, and an external insulating component 11 is arranged between the positive terminal 7 and the sealing plate 2. The negative electrode collector plate 8 is connected to the exposed portion of the negative electrode core 5, and the negative electrode collector plate 8 is electrically connected to the negative terminal 9. An internal insulating component 12 is arranged between the negative electrode collector plate 8 and the sealing plate 2, and an external insulating component 13 is arranged between the negative terminal 9 and the sealing plate 2.

[0046] An insulating sheet 14 is disposed between the electrode body 3 and the outer packaging body 1 so as to wrap the electrode body 3. The sealing plate 2 is provided with a gas discharge valve 15 that breaks when the pressure in the battery case 200 reaches a predetermined value or more and discharges the gas in the battery case 200 to the outside. In addition, the sealing plate 2 is provided with an electrolyte injection hole 16. After the non-aqueous electrolyte is injected into the battery case 200, the electrolyte injection hole 16 is sealed by a sealing plug 17.

[0047] [positive electrode]

[0048] The positive electrode has a positive electrode core and a positive electrode active material layer disposed on the positive electrode core. The positive electrode core can use a foil of a metal such as aluminum that is stable within the potential range of the positive electrode. The positive electrode active material layer preferably includes a positive electrode active material, a conductive material, and a binding material, and is disposed on both sides of the positive electrode core. The positive electrode can be made by, for example, applying a positive electrode active material layer slurry containing a positive electrode active material, a conductive material, and a binding material on the positive electrode core, drying the coating, and then compressing it to form a positive electrode active material layer on both sides of the positive electrode core.

[0049] The positive electrode active material is composed of a lithium metal composite oxide as a main component. As metal elements contained in the lithium metal composite oxide, Ni, Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, W, etc. can be listed. An example of a suitable lithium metal composite oxide is a lithium metal composite oxide containing at least one of Ni, Co, and Mn. As a specific example, lithium metal composite oxides containing Ni, Co, and Mn; lithium metal composite oxides containing Ni, Co, and Al can be listed. It should be noted that inorganic compound particles such as tungsten oxide, aluminum oxide, and compounds containing lanthanide elements can be solidified on the surface of the lithium metal composite oxide particles.

[0050] As the conductive material contained in the positive electrode active material layer, carbon materials such as carbon black, acetylene black, Ketjen black, and graphite can be exemplified. As the binding material contained in the positive electrode active material layer, fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide resin, acrylic resin, polyolefin resin, etc. can be exemplified.

[0051] [negative electrode]

[0052] The negative electrode has a negative electrode core and a negative electrode active material layer disposed on the negative electrode core. The negative electrode core may be made of a metal foil such as copper that is stable within the potential range of the negative electrode. The negative electrode active material layer preferably contains a negative electrode active material and a binding material, and is disposed on both sides of the negative electrode core. The negative electrode can be made by, for example, coating a negative electrode active material layer slurry containing a negative electrode active material and a binding material on the negative electrode core, drying the coating, and then compressing to form a negative electrode active material layer on both sides of the negative electrode core.

[0053] As described below, the negative electrode active material layer includes: coated graphite particles having a first amorphous carbon and a second amorphous carbon having a higher conductivity than the first amorphous carbon fixed on the surface of the graphite particles, styrene-butadiene rubber having an average primary particle size of 150 to 210 nm, and a weight average molecular weight of 3.7×10 5 ~4.3×10 5 At least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt. It should be noted that when the negative electrode active material layer contains carboxymethyl cellulose and carboxymethyl cellulose salt, the weight average molecular weight of carboxymethyl cellulose and carboxymethyl cellulose salt is set to 3.7×10 5 ~4.3×10 5 In this specification, the weight average molecular weight (Mw) refers to a value measured by gel permeation chromatography (GPC).

[0054] The negative electrode active material layer includes coated graphite particles as the negative electrode active material. The coated graphite particles are particles in which two types of amorphous carbon are consolidated on the surface of graphite particles such as natural graphite such as flaky graphite, blocky graphite, amorphous graphite, blocky artificial graphite (MAG), and artificial graphite such as graphitized mesophase carbon microbeads (MCMB). It should be noted that as the negative electrode active material, metals such as Si that alloy with lithium, alloys containing the metal, compounds containing the metal, etc. can be used in combination within the range not impairing the purpose of the present application. Examples of negative electrode active materials other than graphite include SiO x Silicon oxide, etc. shown.

[0055] like Figure 3 As shown in the example, the coated graphite particle 20 is composed of a graphite particle 21 and two types of amorphous carbon fixed on the surface of the graphite particle 21. As described above, the two types of amorphous carbon include a first amorphous carbon and a second amorphous carbon having a higher conductivity than the first amorphous carbon. It is preferred that an amorphous carbon layer 22 composed of the first amorphous carbon is formed on the surface of the graphite particle 21, and an amorphous carbon particle 23 composed of the second amorphous carbon is fixed. The coated graphite particle 20 has high conductivity due to the function of the amorphous carbon.

[0056] The amorphous carbon layer 22 is preferably formed in a manner that covers the entire surface of the graphite particle 21. The amorphous carbon layer 22 is preferably formed in the form of a continuous layer that covers the entire surface of the graphite particle 21. On the other hand, the amorphous carbon particles 23 are scattered on the surface of the graphite particle 21. The amorphous carbon particles 23 are preferably distributed and fixed to the entire surface of the graphite particle 21, and are not concentrated on a part of the surface of the graphite particle 21.

[0057] The first amorphous carbon constituting the amorphous carbon layer 22 is preferably a burnt product of, for example, asphalt. That is, the raw material of the first amorphous carbon can be asphalt. The asphalt can be any of petroleum asphalt and coal asphalt. The amorphous carbon layer 22 is formed by, for example, attaching asphalt to the entire surface of the graphite particle 21 and then firing it at a temperature of 900 to 1500° C., preferably 1200 to 1300° C., in an inert gas atmosphere. The mass ratio of the amorphous carbon layer 22 in the coated graphite particle 20 is preferably 1 to 10 mass %, more preferably 2 to 5 mass %, relative to the total mass of the coated graphite particle 20.

[0058] The amorphous carbon particles 23 may be directly fixed to the surface of the graphite particles 21, or may be fixed to the surface of the graphite particles 21 via the amorphous carbon layer 22. In addition, the amorphous carbon particles 23 may be covered by the amorphous carbon layer 22. For example, a portion of the amorphous carbon particles 23 may be buried in the amorphous carbon layer 22. Figure 3 As exemplified in FIG. 2 , a part of the particle surface of the amorphous carbon particle 23 may not be covered by the amorphous carbon layer 22 but may be exposed. Figure 4 2 is a schematic diagram showing an enlarged cross section of the vicinity of the amorphous carbon particle 23 in the coated graphite particle 20. Figure 4 As shown in FIG. 1 , the amorphous carbon particles 23 preferably have a shape with irregularities on the surface.

[0059] The second amorphous carbon constituting the amorphous carbon particles 23 is preferably, for example, carbon black. Carbon black has high electrical conductivity and a small volume change during charge and discharge, and is therefore suitable as the amorphous carbon particles 23. The average particle size of the amorphous carbon particles 23 can be set to, for example, 30 to 200 nm. The average particle size is calculated by selecting 100 amorphous carbon particles 23 from an electron microscope image of the amorphous carbon particles 23, measuring the longest diameter lengths of each other, and averaging the measured values. In addition, the absorption amount of dibutyl phthalate (DBP) of the amorphous carbon particles 23 can be set to, for example, 35 to 220 mL / 100 g.

[0060] The mass ratio of the amorphous carbon particles 23 in the coated graphite particles 20 is preferably higher than the mass ratio of the amorphous carbon layer 22. That is, it is preferred that the second amorphous carbon is present on the surface of the graphite particles 21 in a larger amount than the first amorphous carbon on a mass basis. The mass ratio of the amorphous carbon particles 23 relative to the total mass of the coated graphite particles 20 is preferably 2 to 15 mass%, more preferably 5 to 9 mass%.

[0061] It should be noted that the presence of amorphous carbon can be confirmed by Raman spectroscopy. The argon laser Raman spectra at 1360 cm -1 The peaks near 1580 cm-1 are derived from amorphous carbon and are hardly observed in graphite carbon. -1 The peaks around 1360cm are peaks unique to graphite carbon. -1 The peak intensity near 1360 ) and 1580cm -1 The peak intensity near 1580 ) ratio (I 1360 / I 1580 ), for example, it is 0.10 or less in the graphite particles 21 and it is 0.13 or more in the coated graphite particles 20.

[0062] The central particle diameter (D50) of the coated graphite particles 20 is, for example, 5 to 20 μm, preferably 8 to 13 μm. The central particle diameter refers to the median particle diameter when the volume cumulative value in the particle size distribution measured by a laser diffraction scattering particle size distribution measuring device (e.g., LA-750 manufactured by HORIBA) reaches 50%. If the central particle diameter (D50) of the coated graphite particles 20 is in this range, the coating property of the negative electrode active material layer slurry is improved, and the adhesion strength of the negative electrode active material layer to the core becomes higher. In addition, the contact points between the particles can be increased, and the conductivity of the negative electrode active material layer is further improved.

[0063] As described above, the negative electrode active material layer contains a weight average molecular weight of 3.7×10 5 ~4.3×10 5 At least one selected from carboxymethyl cellulose and a carboxymethyl cellulose salt. Examples of the carboxymethyl cellulose salt include sodium carboxymethyl cellulose and ammonium carboxymethyl cellulose. At least one selected from carboxymethyl cellulose and a carboxymethyl cellulose salt may function as a binder and may also have a viscosity adjustment function for the negative electrode active material layer slurry.

[0064] In the negative electrode active material layer, at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt is attached to the surface of the coated graphite particles 20. At least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt covers the amorphous carbon particles 23 present on the surface of the coated graphite particles 20. By coating the surface of the amorphous carbon particles 23 with at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt, when the non-aqueous electrolyte secondary battery 100 is stored at a high temperature, the side reaction between the amorphous carbon particles 23 and the non-aqueous electrolyte can be effectively suppressed. Therefore, the high temperature storage characteristics are improved. The weight average molecular weight is 3.7×10 5 ~4.3×10 5 The at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt has a high affinity with the amorphous carbon particles 23 and can effectively cover the amorphous carbon particles 23. It should be noted that if the weight average molecular weight of at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt is less than 3.7×10 5 On the other hand, if the weight average molecular weight of at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt exceeds 4.3×10 5 , at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt is difficult to dissolve in the negative electrode active material layer slurry, making it difficult to form a good negative electrode active material layer without pinholes.

[0065] The content of carboxymethyl cellulose and carboxymethyl cellulose salt is preferably 0.1 to 1% by mass, more preferably 0.2 to 0.8% by mass, relative to the total mass of the negative electrode active material layer. In addition, carboxymethyl cellulose and carboxymethyl cellulose salt are preferably present in an amount of 0.1 to 1% by mass relative to the total mass of the coated graphite particles 20. At this time, the amorphous carbon particles 23 of the coated graphite particles 20 can be efficiently coated with carboxymethyl cellulose and carboxymethyl cellulose salt. In the negative electrode active material layer, the content of styrene-butadiene rubber is preferably set to 0.05 to 1% by mass, more preferably 0.1 to 0.5% by mass, relative to the total mass of the negative electrode active material layer.

[0066] [Spacer]

[0067] The spacer uses a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, etc. The material of the spacer is preferably olefin resins such as polyethylene and polypropylene, cellulose, etc. The spacer can be any one of a single-layer structure and a laminated structure. A heat-resistant layer, etc., can be formed on the surface of the spacer.

[0068] [Non-aqueous electrolyte]

[0069] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt. The non-aqueous solvent may use, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more thereof. The non-aqueous solvent may contain a halogen-substituted body in which at least a portion of the hydrogen in these solvents is replaced by a halogen atom such as fluorine. As examples of the above-mentioned esters, cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone (GBL) and γ-valerolactone (GVL); chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate.

[0070] Examples of electrolyte salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1<x<6, n is 1 or 2), etc. The concentration of the electrolyte salt can be set to 0.8 to 1.8 mol per 1 L of the non-aqueous solvent, for example. The non-aqueous electrolyte may contain difluorophosphate or a lithium salt having an oxalate complex as an anion as the electrolyte salt.

[0071] Hereinafter, the present application will be further described by way of examples, but the present application is not limited to these examples.

[0072] <Example 1>

[0073] [Production of positive electrode]

[0074] As the positive electrode active material, LiNi 0.35 Co 0.35 Mn 0.30 The positive electrode active material, PVdF and carbon black were mixed in a mass ratio of 90:3:7, and N-methyl-2-pyrrolidone was added while kneading to prepare a positive electrode active material layer slurry. Next, the positive electrode active material layer slurry was applied to both sides of a strip-shaped positive electrode core formed of an aluminum foil with a thickness of 13 μm, and the coating was dried. The dried coating was filled with a filling density of 2.5 g / cm 3 After being compressed in a manner, the positive electrode is cut into a specified electrode size to produce a positive electrode having a positive electrode active material layer formed on both sides of the positive electrode core. It should be noted that the positive electrode is provided with a positive electrode core exposed portion for connecting a positive electrode collector plate at one end in the width direction along the length direction of the positive electrode.

[0075] [Production of coated graphite particles]

[0076] The graphite particles obtained by modifying natural graphite into spherical shapes and the second amorphous carbon have a BET specific surface area of ​​42 m 2 / g of carbon black are mechanically mixed to prepare mixed particles in which carbon black particles are fixed on the surface of graphite particles, and pitch (a raw material of the first amorphous carbon) is added to the mixed particles and mixed so that the pitch is attached to the surface of the mixed particles. Graphite particles, pitch and carbon black are mixed in a mass ratio of 90:3:7. The graphite particles with pitch and carbon black attached to the surface are calcined at a temperature of 1250°C for 24 hours in an inert gas atmosphere, and the calcined product is crushed to prepare coated graphite particles in which the calcined product of pitch as the first amorphous carbon and carbon black as the second amorphous carbon are fixed on the surface of the particles.

[0077] In the coated graphite particles, the burned product of pitch covers the entire surface of the graphite particles to form an amorphous carbon layer, and amorphous carbon particles composed of carbon black are fixed to the surface of the graphite particles.

[0078] [Production of negative electrode]

[0079] As the negative electrode active material, the above-mentioned coated graphite particles were used. The negative electrode active material was mixed with a graphite having a weight average molecular weight of 4.0×10 5 The negative electrode active material layer slurry is prepared by mixing the sodium salt of carboxymethyl cellulose (CMC-Na), adding water while kneading, and then adding a dispersion of styrene-butadiene rubber (SBR) with an average primary particle size of 180 nm. The negative electrode active material, CMC-Na and SBR are mixed in a mass ratio of 99:0.6:0.4. Next, the negative electrode active material layer slurry is applied to both sides of a strip-shaped negative electrode core formed by a copper foil with a thickness of 8 μm, and the coating is dried. The dried coating is filled with a filling density of 1.2 g / cm 3 After being compressed in a manner, it is cut into a specified electrode size to produce a negative electrode having a negative electrode active material layer formed on both sides of the negative electrode core. It should be noted that the negative electrode is provided with a negative electrode core exposed portion for connecting a negative electrode collector plate at one end in the width direction along the length direction of the negative electrode.

[0080] [Preparation of non-aqueous electrolyte]

[0081] A non-aqueous electrolyte solution was prepared by dissolving LiPF6 in a mixed solvent obtained by mixing EC, EMC and DMC in a volume ratio of 3:3:4 (1 atmospheric pressure, 25°C) to a concentration of 1.15 M.

[0082] [Fabrication of non-aqueous electrolyte secondary battery]

[0083] The positive electrode and the negative electrode are wound with a strip-shaped separator made of polyolefin, and pressed into a flat shape to make a flat wound electrode body. At this time, the positive electrode and the negative electrode are wound in such a way that the exposed portion of the positive electrode core is located at one end of the winding axis direction of the electrode body and the exposed portion of the negative electrode core is located at the other end of the winding axis direction. The positive electrode collector electrically connected to the positive terminal and mounted on the sealing plate is welded to the exposed portion of the positive electrode core. The negative electrode collector electrically connected to the negative terminal and mounted on the sealing plate is welded to the exposed portion of the negative electrode core. Thereafter, the wound electrode body covered with an insulating sheet is inserted into the outer packaging body. The sealing plate is welded to the outer packaging body, and the opening of the outer packaging body is sealed with a sealing plate. After the above-mentioned non-aqueous electrolyte is injected from the electrolyte injection hole provided in the sealing plate, the electrolyte injection hole is sealed with a sealing plug to obtain a non-aqueous electrolyte secondary battery with a rated capacity of 4.1Ah.

[0084] <Example 2>

[0085] In the preparation of the coated graphite particles, a second amorphous carbon having a BET specific surface area of ​​37 m 2 / g of carbon black to replace the BET specific surface area of ​​42m 2 A battery was produced in the same manner as in Example 1 except that the carbon black was reduced by 1.0 g.

[0086] <Example 3>

[0087] In the preparation of the coated graphite particles, a second amorphous carbon having a BET specific surface area of ​​47 m 2 / g of carbon black to replace the BET specific surface area of ​​42m 2 A battery was produced in the same manner as in Example 1 except that the carbon black was reduced by 1.0 g.

[0088] <Example 4>

[0089] A battery was produced in the same manner as in Example 1, except that SBR having an average primary particle size of 150 nm was used instead of SBR having an average primary particle size of 180 nm in the production of the negative electrode.

[0090] <Example 5>

[0091] A battery was produced in the same manner as in Example 1, except that SBR having an average primary particle size of 210 nm was used instead of SBR having an average primary particle size of 180 nm in the production of the negative electrode.

[0092] <Example 6>

[0093] In the preparation of the negative electrode, a weight average molecular weight of 3.7×10 5 The weight average molecular weight of CMC-Na is 4.0×10 5A battery was produced in the same manner as in Example 1 except that the CMC-Na was used.

[0094] <Example 7>

[0095] In the preparation of the negative electrode, a weight average molecular weight of 4.3×10 5 The weight average molecular weight of CMC-Na is 4.0×10 5 A battery was produced in the same manner as in Example 1 except that the CMC-Na was used.

[0096] <Comparative Example 1>

[0097] A battery was produced in the same manner as in Example 1 except for the following points.

[0098] In the preparation of the coated graphite particles, a second amorphous carbon having a BET specific surface area of ​​52 m 2 / g of carbon black to replace the BET specific surface area of ​​42m 2 / g of carbon black.

[0099] In the preparation of the negative electrode, a weight average molecular weight of 3.3×10 5 The weight average molecular weight of CMC-Na is 4.0×10 5 of CMC-Na.

[0100] In the preparation of the negative electrode, SBR having an average primary particle size of 130 nm was used instead of SBR having an average primary particle size of 180 nm.

[0101] <Comparative Example 2>

[0102] In the preparation of the negative electrode, a weight average molecular weight of 4.0×10 5 The weight average molecular weight of CMC-Na is 3.3×10 5 A battery was produced in the same manner as in Comparative Example 1 except that 1% CMC-Na was used.

[0103] <Comparative Example 3>

[0104] A battery was produced in the same manner as in Comparative Example 2, except that SBR having an average primary particle size of 180 nm was used instead of SBR having an average primary particle size of 130 nm in the production of the negative electrode.

[0105] <Comparative Example 4>

[0106] In the preparation of the coated graphite particles, a second amorphous carbon having a BET specific surface area of ​​42 m 2 / g of carbon black to replace the BET specific surface area of ​​52m 2 A battery was produced in the same manner as in Comparative Example 1 except that the carbon black was reduced by 1.0 g.

[0107] <Comparative Example 5>

[0108] A battery was produced in the same manner as in Comparative Example 4, except that SBR having an average primary particle size of 180 nm was used instead of SBR having an average primary particle size of 130 nm in the production of the negative electrode.

[0109] <Comparative Example 6>

[0110] In the preparation of the coated graphite particles, a second amorphous carbon having a BET specific surface area of ​​42 m 2 / g of carbon black to replace the BET specific surface area of ​​52m 2 A battery was produced in the same manner as in Comparative Example 2 except that the carbon black was reduced by 1.5 g / cm2.

[0111] [Evaluation of low temperature regeneration characteristics]

[0112] The low-temperature regeneration characteristics (regeneration value) of the nonaqueous electrolyte secondary batteries described in Examples 1 to 7 and Comparative Examples 1 to 6 were determined by the following method.

[0113] (1) Charge at 25°C until the depth of charge (SOC) reaches 50%.

[0114] (2) A battery with a SOC of 50% was charged at -30°C for 10 seconds at currents of 1.6C, 3.2C, 4.8C, 6.4C, 8.0C, and 9.6C.

[0115] (3) The battery voltage just after charging for 10 seconds was measured, and the battery voltage was plotted for each current value to find the current value IP (A) when the battery voltage (V) corresponding to 100% SOC was reached. The current value IP was multiplied by the battery voltage (V) corresponding to 100% SOC to calculate the regeneration value (W). In Table 1, as the low-temperature regeneration characteristic (regeneration value), the relative value when the regeneration value of the battery of Comparative Example 1 was set to 100 is shown.

[0116] [Determination of initial discharge capacity]

[0117] For the nonaqueous electrolyte secondary batteries described in Examples 1 to 7 and Comparative Examples 1 to 6, the initial discharge capacity was determined by the following method.

[0118] (1) The battery was charged at a constant current of 4 A until the battery voltage reached 4.1 V, and then charged at a constant voltage of 4.1 V (total of 2 hours).

[0119] (2) Discharge at a constant current of 2 A until the battery voltage reaches 3.0 V, and then discharge at a constant voltage of 3.0 V (3 times in total). The discharge capacity at this time is recorded as the initial discharge capacity.

[0120] [Evaluation of cycle characteristics]

[0121] For the battery after the initial discharge capacity was measured, the cycle characteristics (capacity retention rate after cycles) were determined by the following method.

[0122] (1) Charge at a constant current of 8A until the battery voltage reaches 4.1V.

[0123] (2) Pause for 10 seconds.

[0124] (3) Discharge at a constant current of 8A until the battery voltage reaches 3.0V.

[0125] (4) (1) to (3) were defined as one cycle, and 400 cycles were performed at 60°C.

[0126] (5) Under the condition of 25° C., the battery was charged at a constant current of 4 A until the battery voltage reached 4.1 V, and then charged at a constant voltage of 4.1 V (total 2 hours).

[0127] (6) At 25° C., the battery was discharged at a constant current of 2 A until the battery voltage reached 3.0 V, and then discharged at a constant voltage of 3.0 V (total 3 hours). The discharge capacity at this time was recorded as the discharge capacity after the cycle.

[0128] (7) The capacity retention rate after the cycle was calculated by dividing the discharge capacity after the cycle by the initial discharge capacity.

[0129] In Table 1, as the cycle characteristics (capacity retention rate after cycles), relative values ​​are shown when the capacity retention rate after cycles of the battery of Comparative Example 1 is set to 100.

[0130] [Evaluation of high temperature storage characteristics]

[0131] For the battery after the initial discharge capacity was measured, the high-temperature storage characteristics (capacity retention rate after high-temperature storage) were determined by the following method.

[0132] (1) At 25°C, charge until the depth of charge (SOC) reaches 80%.

[0133] (2) The battery with a SOC of 80% was stored at 75°C for 56 days.

[0134] (3) The battery was discharged at a constant current of 2 A until the battery voltage reached 3.0 V, and then discharged at a constant voltage of 3.0 V (total of 3 hours).

[0135] (4) The battery was charged at a constant current of 4 A until the battery voltage reached 4.1 V, and then charged at a constant voltage of 4.1 V (total of 2 hours).

[0136] (5) The battery was discharged at a constant current of 2 A until the battery voltage reached 3.0 V, and then discharged at a constant voltage of 3.0 V (3 hours in total). The discharge capacity at this time was recorded as the post-storage discharge capacity.

[0137] (6) The capacity retention rate after high-temperature storage was calculated by dividing the discharge capacity after storage by the initial discharge capacity.

[0138] In Table 1, as the high-temperature storage characteristics (capacity retention rate after high-temperature storage), relative values ​​are shown when the capacity retention rate after high-temperature storage of the battery of Comparative Example 1 is set to 100.

[0139] [Table 1]

[0140]

[0141] In Comparative Example 3, the BET specific surface area of ​​carbon black as amorphous carbon particles is 52 m 2 / g, the cycle characteristics become lower.

[0142] In Comparative Example 6, the average primary particle size of the styrene-butadiene rubber was 130 nm, and the cycle characteristics and low-temperature regeneration characteristics were low.

[0143] In Comparative Example 5, the weight average molecular weight of the sodium salt of carboxymethyl cellulose is 3.3×10 5 , high temperature storage characteristics become lower.

[0144] On the other hand, the BET specific surface area of ​​carbon black, which is amorphous carbon particles composed of the second amorphous carbon, is 37 to 47 m 2 / g, the average primary particle size of styrene-butadiene rubber is 150-210 nm, and the weight average molecular weight of sodium salt of carboxymethyl cellulose is 3.7×10 5 ~4.3×10 5 In Examples 1 to 7, the low-temperature regeneration characteristics, cycle characteristics, and high-temperature storage characteristics are excellent.

Claims

1. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, The negative electrode comprises: graphite particles coated with amorphous carbon on the surface of the graphite particles, styrene-butadiene rubber, and at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt. The amorphous carbon contained in the coated graphite particles includes an amorphous carbon layer composed of first amorphous carbon and amorphous carbon particles composed of second amorphous carbon. The electrical conductivity of the second amorphous carbon is higher than that of the first amorphous carbon. The BET specific surface area of ​​the amorphous carbon particles is 37 m 2 / g~42m 2 / g, The average primary particle size of the styrene-butadiene rubber is 150 nm to 210 nm. The weight average molecular weight of at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt is 3.7×10 5 ~4.3×10 5 .

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The first amorphous carbon is a burned product of pitch.

3. The nonaqueous electrolyte secondary battery according to claim 1 or 2, wherein: The second amorphous carbon is carbon black.

4. A method for manufacturing a non-aqueous electrolyte secondary battery, wherein: The nonaqueous electrolyte secondary battery comprises a positive electrode, a negative electrode and a nonaqueous electrolyte. The negative electrode comprises: graphite particles coated with amorphous carbon on the surface of the graphite particles, styrene-butadiene rubber, and at least one selected from carboxymethyl cellulose and carboxymethyl cellulose salt. The amorphous carbon contained in the coated graphite particles includes an amorphous carbon layer composed of first amorphous carbon and amorphous carbon particles composed of second amorphous carbon. The electrical conductivity of the second amorphous carbon is higher than that of the first amorphous carbon. The coated graphite particles are prepared by attaching a BET specific surface area of ​​37 m 2 / g~42m 2 / g of the amorphous carbon particles and the graphite particles as the raw material of the first amorphous carbon are heated to convert the raw material of the first amorphous carbon into the first amorphous carbon, The manufacturing method comprises the following steps: Prepare a styrene-butadiene rubber containing the coated graphite particles, an average primary particle size of 150 nm to 210 nm, and a weight average molecular weight of 3.7×10 5 ~4.3×10 5 a step of preparing a negative electrode active material layer slurry containing at least one selected from carboxymethyl cellulose and a carboxymethyl cellulose salt; The process of coating the negative electrode active material layer slurry on the negative electrode core; and A step of drying the negative electrode active material layer slurry.

5. The method for manufacturing a non-aqueous electrolyte secondary battery according to claim 4, wherein: The raw material of the first amorphous carbon is pitch.

6. The method for producing a non-aqueous electrolyte secondary battery according to claim 4 or 5, wherein: The second amorphous carbon is carbon black.